1980
DOI: 10.1071/rj9800067
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the diets of sheep and cattle grazing a semi-arid Chenopod shrubland.

Abstract: Samples of the diets of oesophageally fistulated sheep and cattle grazing a semi-arid chenopod shrubland dominated by bladder saltbush (Atrip!ex ~'esicaria Hew. ex Benth.) were collected over a four year period. Seasonal condiiions varied from very wet to near drought. The diets of the two herbivores were different on all sampling occasions. However, it can be generalized that overall, sheep had a greater grass component in their diets and that cattle in compensation ate more saltbush than did sheep. Both shee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
1

Year Published

1988
1988
2015
2015

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 9 publications
1
17
1
Order By: Relevance
“…A direct effect of grazing in chenopod shrublands is to reduce plant richness, and plant and litter cover (e.g. Graetz and Wilson 1980). Given that vegetation type is an important indicator of phosphatase activity in soils (Bell et al 2013).…”
Section: Direct and Indirect Effects Of Grazing On Indices Of Multifumentioning
confidence: 98%
See 1 more Smart Citation
“…A direct effect of grazing in chenopod shrublands is to reduce plant richness, and plant and litter cover (e.g. Graetz and Wilson 1980). Given that vegetation type is an important indicator of phosphatase activity in soils (Bell et al 2013).…”
Section: Direct and Indirect Effects Of Grazing On Indices Of Multifumentioning
confidence: 98%
“…Grazing-induced trampling and herbivory reduce the size of Atriplex and Maireana shrubs (Graetz and Wilson 1980) 7 Grazing-induced trampling compacts surface soils, reducing macroporosity, increasing soil bulk density (Laycock and Conrad 1981) and reducing soil microbial populations (Fterich et al 2011) and therefore soil function. 8 (+) Shrubs provide physical protection against trampling by herbivores (Eldridge et al 2013;Smit et al 2007).…”
Section: Experimental Designmentioning
confidence: 99%
“…The cover scores of the remaining eight species were too low to ascertain whether they represent taxa affected by their position in the paddocks or not. While sheep prefer grasses and annual forbs over most chenopod shrubs because of the high salt content of the latter (Graetz & Wilson, 1980, 1984, the ephemeral availability of the first two forces stock to consume shrub forage for most of the time. The periods of rest provided by ephemeral vegetation availability may be important for the recovery of several chenopod populations, including A. vesicaria (Hunt, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Most of the studies on the resilience of Australian chenopods to browsing and drought have been conducted in semi-arid areas grazed by sheep, which browse M. astrotricha more intensively but A. vesicaria less intensively than cattle (Graetz and Wilson, 1980). A previous experiment at Roxby Downs, in arid South Australia, showed that A. vesicaria and M. astrotricha were resilient to intensive spates of cattle browsing during favourable seasons (Read, 1999).…”
Section: Introductionmentioning
confidence: 98%